Handover Analysis of Data and VoIP Services in 802.11b/g/n Wireless LAN - Imam Prasetyo; Muhammad Anif; Ari Sriyanto Nugroho; Subuh Pramono; Sarono Widodo; Sidiq S. Hidayat (Institute of Advanced Engineering and Science, 2014)
IEEE 802.11b/g/n WLAN with conventional ESS infrastructure doesn’t support handover feature. Handover feature allows user to migrate services between APs without losing connection. Handoff latency is one problem in WLAN to perform real-time application such as VoIP. To bring seamless handover and QoS guarantee in ESS network, we propose five network optimization methods i.e.configuring overlapping area of APs, placing APs in one roaming domain, using the same SSID and security mode, choosing APs channel by margin of 5, and configuring APs as DHCP forwarder. Handover test is done by sniffing on the client that experienced handover. In the result, there are three steps in Layer 2 handoff, i.e. probing, authentication, and re-association with maximum handoff latency is 325.02 ms in data services and 67.412 ms in VoIP. In VoIP services, one way delay is 39.985 - 49.18 ms, one way jitter is 9.45 - 19.57 ms, and the packet loss is 0 - 0.548%. Overall, the built network system is able to guarantee QoS in handover case, both in data and VoIP services.